2018
DOI: 10.1016/j.cherd.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Application of high-frequency impedancemetry approach in measuring the deposition velocities of biomass and sand slurry flows in pipelines

Abstract: Since the lower limit to operating velocities in slurry transport systems is influenced by deposition conditions, measuring the "deposition velocity" is an essential step in slurry pipelines' design and operation. This study proposes a new experimental technique in measuring deposition velocities in slurry pipeline transport called the high-frequency impedancemetry approach. This non-invasive technique of measuring electrical properties of substances, based on their frequency-dependent behavior, was applied us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Visual observations (despite the dark brown background, which made the analysis challenging) showed no bed formation for 6.4 mm particle size wheat straw-water slurries across the whole range of mass concentrations (C m = 5%-30%) running down the inclined pipe section of any of the slopes (-7° to +21°) used in the current investigation, even at the minimal slurry velocity of 0.5 m s -1 . This outcome was on par with an earlier study on the deposition velocity of biomass particles, in which it was discovered that this velocity was 0.21-0.28 m s -1 for slurries of wheat straw particles with d 50 = 4.81 mm for C m = 5%-20% in horizontal flows (Vaezi et al, 2018). Further, in the earlier work, the terminal settling velocity (v t ) of several particle lengths (5-30 mm) of wheat straw was evaluated as 13-17 mm s -1 in a quiescent medium and it was found that these particles were buoyant (i.e., (v m / v t ) ≤ 0.021), specifically for v m ≥ 0.5 m s -1 and particle sizes of 5-10 mm (Javed et al, 2022a).…”
Section: Wheat Straw Particlessupporting
confidence: 80%
“…Visual observations (despite the dark brown background, which made the analysis challenging) showed no bed formation for 6.4 mm particle size wheat straw-water slurries across the whole range of mass concentrations (C m = 5%-30%) running down the inclined pipe section of any of the slopes (-7° to +21°) used in the current investigation, even at the minimal slurry velocity of 0.5 m s -1 . This outcome was on par with an earlier study on the deposition velocity of biomass particles, in which it was discovered that this velocity was 0.21-0.28 m s -1 for slurries of wheat straw particles with d 50 = 4.81 mm for C m = 5%-20% in horizontal flows (Vaezi et al, 2018). Further, in the earlier work, the terminal settling velocity (v t ) of several particle lengths (5-30 mm) of wheat straw was evaluated as 13-17 mm s -1 in a quiescent medium and it was found that these particles were buoyant (i.e., (v m / v t ) ≤ 0.021), specifically for v m ≥ 0.5 m s -1 and particle sizes of 5-10 mm (Javed et al, 2022a).…”
Section: Wheat Straw Particlessupporting
confidence: 80%
“…In addition, piping systems frequently contain horizontal and vertical portions and changes of direction via elbows and tees, making the design of conveying systems complex. Therefore, the prediction of flow patterns, pressure drops, sedimentation and erosion rates, transport rates, clustering, clogging, and jamming in liquid-solid piping systems re-mains challenging [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Slurry pipeline transport is a commercially viable mode of transporting solid commodities as an alternative to truck and rail; nevertheless, it is a complex process (Vaezi, Verma and Kumar, 2018). The environmental and economic advantages of this method rather than by road or rail are being increasingly recognized by mining companies (Bhabra, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that viscosity plays an important role in the sand minimum transport condition. A new experimental technique to measure deposition velocities in pipeline transport of solids was proposed by (Vaezi, Verma and Kumar, 2018). The authors used high-frequency impedancemetry, a non-invasive technique, to determine the deposition velocities of sand-water and biomass-water mixtures over a wide range of concentrations and pumped over a range of velocities much wider than the common industrial practice.…”
Section: Introductionmentioning
confidence: 99%